Vulkanasche und Rechte der Fluggäste. - Müller-Rostin, Wolf (Deutscher Verkehrs-Verl., 2010)
Millionen Flugreisende saßen auf europäischen und außereuropäischen Flughäfen teilweise mehrere Tage fest, als wegen der vulkanaschebedingten Sperrung des europäischen Luftraums ihre Maschinen nicht starten konnten. Vielen dieser gestrandeten Flugreisenden kam allerdings eine EU-Verordnung zu Hilfe, die ihnen im Falle der Flugannullierung Ansprüche auf gewisse Betreuungs- und Unterstützungsleistungen gegenüber dem Luftfahrtunternehmen, das den Flug ausführen sollte, einräumt.

For several days, millions of airline passengers were stranded at both European and non-European airports due to the closure of Europe's airspace caused by volcanic ash that prevented aircraft from taking off. EU Regulation 261/2004, which covers certain remedies for passengers subject to denied boarding, flight cancellation or long delay, assisted many of the stranded passengers, because it obligates the air carriers to provide care (hotel accommodation, telecommunication) and assistance (reimbursement, re-routing) to passengers even in cases of force majeure. The author raises the question whether a liability even in cases where the transportation is interrupted for reasons completely outside the control of the air carrier can be considered proportionate well balanced between the interest of the passengers and that of the carriers. Harmonization of the obligations of all modes of transportation is urgently needed.
Volcanic ash and the rights of air travelers.
Keywords: Verkehr; Luftverkehr; Haftung; Luftverkehrsunternehmen; Fluggesellschaft; Fluggast; Passagier; Kostenerstattung; Reisekosten; EU-Verordnung